2014
DOI: 10.1155/2014/260187
|View full text |Cite
|
Sign up to set email alerts
|

Trusted Computing Strengthens Cloud Authentication

Abstract: Cloud computing is a new generation of technology which is designed to provide the commercial necessities, solve the IT management issues, and run the appropriate applications. Another entry on the list of cloud functions which has been handled internally is Identity Access Management (IAM). Companies encounter IAM as security challenges while adopting more technologies became apparent. Trust Multi-tenancy and trusted computing based on a Trusted Platform Module (TPM) are great technologies for solving the tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Even though the complexities mixed up with the computation are addressed, only, certain resources like CPU and disk have been incorporated. To address the challenges involved in the security aspect of the cloud computing environment, cloud authentication [15] is to be enhanced to provide a resourceful mechanism against a phishing attack in the initial stages.…”
Section: Related Workmentioning
confidence: 99%
“…Even though the complexities mixed up with the computation are addressed, only, certain resources like CPU and disk have been incorporated. To address the challenges involved in the security aspect of the cloud computing environment, cloud authentication [15] is to be enhanced to provide a resourceful mechanism against a phishing attack in the initial stages.…”
Section: Related Workmentioning
confidence: 99%
“…Remote attestation can be used to establish trust relationship in cloud. At present, it has become a new favorite in the cloud computing security research field that trusted computing is used to solve the cloud computing security, Reference [11] constructs a trusted cloud platform using the trusted platform module (TPM) to guarantee the security of the cloud platform. Reference [12] also uses remote attestation in trusted computing to solve the cloud computing security problems.…”
Section: Trusted Access and Remote Attestationmentioning
confidence: 99%
“…It is usually performed through email or instant messaging when the victims are directed to a forged website and encouraged to provide their sensitive information. As an example, banking websites are very common targets to be forged [3].…”
Section: Phishing and Pharmingmentioning
confidence: 99%
“…Ghazizadeh et al in [3] suggested a model in order to solve identity theft in the cloud. This model incorporates trusted computing, Federated Identity Management, and OpenID Web SSO.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation